Comparison of volumetric‐modulated arc therapy and dynamic conformal arc treatment planning for cranial stereotactic radiosurgery. (8th January 2016) - Molinier, Jessica; Kerr, Christine; Simeon, Sebastien; Ailleres, Norbert; Charissoux, Marie; Azria, David; Fenoglietto, Pascal
Abstract : The aim was to analyze arc therapy techniques according to the number and position of the brain lesions reported by comparing dynamic noncoplanar conformal arcs (DCA), two coplanar full arcs ( RA C ) with volumetric‐modulated arc therapy (VMAT), multiple noncoplanar partial arcs with VMAT ( RA NC ), and two full arcs with VMAT and 10° table rotation ( RA T ). Patients with a single lesion (n = 10), multiple lesions (n = 10) or a single lesion close to organs at risk (n = 5) and previously treated with DCA were selected. For each patient, the DCA treatment was replanned with all VMAT techniques. All DCA plans were compared with VMAT plans and evaluated in regard to the different quality indices and dosimetric parameters. For single lesion, homogeneity index (HI) better results were found for the RA NC technique ( 0.17 ± 0.05 ) compared with DCA procedure ( 0.27 ± 0.05 ). Concerning conformity index (CI), the RA T technique gave higher and better values ( 0.85 ± 0.04 ) compared with those obtained with the DCA technique ( 0.77 ± 0.05 ). DCA improved healthy brain protection ( 8.35 ± 5.61   cc vs. 10.52 ± 6.40   cc for RA NC ) and reduced monitor unit numbers ( 3046 ± 374 MU vs. 4651 ± 736 for RA NC ), even if global room occupation was higher. For multiple lesions, VMAT techniques provided better HI (0.16) than DCA ( 0.24 ± 0.07 ). The CI was improved with RA T ( 0.8 ± 0.08 for RA T vs. 0.71 ± 0.08 for DCA). The V 10 Gy healthy brain was better protected with DCA ( 9.27 ± 4.57   cc ). Regarding the MU numbers: RA NC < RA T < RA C < DCA . For a single lesion close to OAR, RA T achieved high degrees of homogeneity ( 0.27 ± 0.03 vs. 0.53 ± 0.2 for DCA) and conformity ( 0.72 ± 0.06 vs. 0.56 ± 0.13 for DCA) while sparing organs at risk ( D max = 12.36 ± 1.05   Gy vs. 14.12 ± 0.59   Gy for DCA, and D mean = 3.96 ± 3.57   Gy vs. 14.72 ± 3.28   Gy for DCA). On the other hand, MU numbers were lower with DCA ( 2254 ± 190 MU vs. 3438 ± 457 MU for RA NC ) even if overall time was inferior with RA C . For a single lesion, DCA provide better plan considering low doses to healthy brain even if quality indexes are better for the others techniques. For multiple lesions, RA NC seems to be the best compromise, due to the ability to deliver a good conformity and homogeneity plan while sparing healthy brain tissue. For a single lesion close to organs at risk, RA T is the most appropriate technique. PACS numbers: 87.55. dk, 87.56.bd